Tall Man lettering and potential prescription errors: a time series analysis of 42 children's hospitals in the USA over 9 years. Issue 4 (3rd November 2015) - Zhong, Wenjun; Feinstein, James A; Patel, Neil S; Dai, Dingwei; Feudtner, Chirs
Abstract : Background: Despite the widespread implementation of Tall Man lettering, little evidence exists regarding whether this technique has reduced drug errors due to look-alike sound-alike (LA-SA) drug names. This study evaluated rates of potential LA-SA drug errors in the drug management process through to the point of dispensing before and after implementation of Tall Man lettering in 2007. Methods: We used detailed pharmacy data for paediatric inpatients (<21 years old) from 42 children's hospitals in 2004–2012. After prespecifying a set of 8 potential LA-SA drug error patterns we searched within each hospitalisation for the occurrence of one of these patterns for a total of 12 LA-SA drug pairs deemed highly relevant to paediatric inpatients. To assess for potential change of error rates before and after Tall Man lettering implementation, we performed segmented regression analyses for each of 11 LA-SA drug pairs (because 1 pair had no detected potential errors) and for the overall total errors of all 11 LA-SA drug pairs. Results: Among 1 676 700 hospitalisations, no statistically significant change was detected for either the intercept or the slope of LA-SA error rate for each of the 11 drug pairs or for the combined error rate. In a sensitivity analysis of the moving average of the potential error rate over the entire study period, no downward trend in potential LA-SA drug error rates was evident over any time period 2004 onwards. Conclusions: Implementation of Tall Man lettering in 2007 was not associated with a reduction in the potential LA-SA error rate. Whether Tall Man lettering is effective in clinical practice warrants further study.